PELATIHAN MANAJEMEN INVESTASI EMAS DIGITAL BAGI PEKERJA MELALUI APLIKASI BYOND BY BSI - Rahmawati, Herlini Sanika; Darmawan, Indra Manggala Dwi; Romlah, Siti; Soebandono, Mochamad Raka Putra; Kartini, Ida Ayu Nuh (BESIRU : Jurnal Pengabdian Masyarakat, 2025)
The rapid development of digital technology has transformed financial services and expanded access to modern investment instruments, including digital gold. This community service program aimed to enhance factory workers understanding of sharia compliant digital gold investment using the BYOND by BSI application. Conducted online via Zoom with 50 participants, the training consisted of pre-test, material delivery, feature demonstration, simulation practice, discussion, and post-test. The program introduced investment fundamentals, sharia principles, and technical application use. Results indicated a significant improvement in participants knowledge, supported by moderate N-Gain values and a statistically significant paired t-test. This activity highlights the effectiveness of digital financial literacy training in strengthening workers investment readiness and promoting inclusive sharia-based financial practices.